The Categorization Process from the Becoming Perspective - Brenner Beauchamp Weber, Tiziana (Organizações & Sociedade, 2024)
Current approaches to market categories are predominantly rooted in a substantialist ontology, where categories are perceived as static entities with a consensual symbolic composition among producers, consumers, and intermediaries. From this standpoint, categories change from one phase to another, followed by stabilization, with market actors periodically reaching a consensus on the symbolic constitution of a category. This theoretical essay argues for a paradigm shift toward viewing the symbolic constitution of market categories as an ongoing process aligned with the ontology of becoming rather than adhering to a substantialist perspective. A theoretical model is proposed to support this argument, grounded on three interconnected components: market actors, interactional processes, and the radial structure of categories. The model posits that categorization is an ongoing process of symbolic constitution facilitated by interactional processes among market participants. This process results in a categorical radial structure characterized by a core containing relatively consensual meanings and a periphery featuring a greater dispersion of dissenting meanings. The continuous interplay between central and peripheral meanings drives the evolution of market categories, akin to the internal contradictions observed in Hegelian dialectics.